Financial Report Fraud Determinants (Banking and Insurance Sub-Sector Companies on the Indonesia Stock Exchange 2017-2021) - Anton; Fernando, Edison; Estu, Ahmad Zulkarnain; Eddy, Pujiono; Andi (First Ciera Publisher, 2023)
The purpose of this research is to examine and analyze financial stability, external pressure, financial targets, personal financial need, the nature of the industry, ineffective monitoring, and rationalization of fraudulent financial statements. The research was conducted on banking and insurance sub-sector companies with annual financial reports for the 2017-2021 period which are listed on the Indonesia Stock Exchange (IDX). The population in this study were all banking and insurance sub-sector companies listed on the Indonesia Stock Exchange. The samples used in this study were 55 companies taken by purposive sampling method. The data analysis technique used is multiple linear regression analysis using Smart PLS software. The results of the study show that financial stability and external pressure have a significant effect on fraudulent financial statements.